Exacerbating risks and diminishing rights for ‘at-risk’ prisoners - Harris, Alexis (Criminology & criminal justice, 2018)
At-Risk Units (ARUs) are dedicated facilities established in New Zealand prisons to assist those considered to be ‘at risk’ of self-harm or suicide. Their remit is ostensibly care-based and rights-conscious, with authorities noting that ARUs preserve the ‘right to life’. Drawing upon research within two correctional sites, alongside analysis of recent documents from oversight bodies and courts, this article considers ARU operations. It is argued that, all too often, ARUs have undermined humane practices towards suicidal or ‘at-risk’ prisoners. Four problems are apparent: (1) ARUs are misused and overused in such a way that secure punishment, rather than care, is prioritized; (2) within a context of ‘lesser eligibility’, ARUs operationalize degrading conditions and treatments towards prisoners; (3) humane treatments are further diminished by a correctional approach to prioritize legal or bureaucratic compliance; and (4) authorities avoid institutional sanction for prisoner harms or deaths, particularly through an emphasis on personal responsibilization or blame. The end-result is that ARUs are regularly operationalized in ways that exacerbate risks and diminish rights for prisoners. A question remains about their fundamental use as an appropriate response to those who suffer mental health distress within penal environments.